Hydrographic Magnetic Resonance Imaging of the Fetal Eye - Paquette, Lisa B.; Jackson, Hollie A.; Tavaré, C Jane; Panigrahy, Ashok (American Journal of Perinatology, 2012)
Previous work has shown that fetal hydrographic magnetic resonance imaging (MRI) provided additional information complementary to T2-weighted single-shot fast spin echo (ssFSE) images. The objective of this study was to determine if hydrographic MRI provides better conspicuity of fetal eye structures compared with ssFSE MRI. ssFSE and hydrographic images were retrospectively examined in 82 consecutive fetal studies with normal central nervous system without sensitivity encoding. Relative signal intensity values on ssFSE and hydrographic MRI were obtained for vitreous and sclera. Ratios of the signal intensity of vitreous to the signal intensity of sclera were calculated to determine conspicuity. Similar measurements were obtained in a smaller separate data set (n = 41) using hydrographic imaging with sensitivity encoding techniques. The hydrographic images significantly demonstrated greater conspicuity (ratio of vitreous to sclera) than ssFSE images. This was consistent for both sensitivity encoding and no-sensitivity encoding groups. The difference in conspicuity was on average approximately two times greater in the hydrographic images compared with ssFSE images. Hydrographic MRI of the fetal eye provides on average two times greater conspicuity of fetal eye structures than ssFSE imaging. This enhancement is not affected by gestational age or the use of sensitivity encoding parallel imaging techniques.
Keywords: SENSE technique; conspicuity measurement; single-shot fast; spin echo imaging; hydrographic imaging